2019
DOI: 10.3390/agriculture9090194
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Ecological Performance of Miscanthus (Miscanthus × giganteus Greef et Deuter) through Intercropping with Woad (Isatis tinctoria L.) and Yellow Melilot (Melilotus officinalis L.)

Abstract: Miscanthus is a promising high-yielding and low-input perennial biomass crop. However, as miscanthus does not produce nectar, it provides less support for pollinators than other perennial biomass crops, such as cup plant, Virginia mallow, or wild plant mixtures. This study discusses whether miscanthus could be intercropped with flower-rich biennial wild plants to further enhance its ecological functioning. In 2017, a demonstration plot was established in southwest Germany with two miscanthus intercropping regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…In the later years 2018 and 2019, however, there were no significant differences between REF and MUM [34]. This is in line with a finding from a recent study on intercropping miscanthus and legumes, in which similar effects were reported [47]. However, the potentially higher yielding variant REF was water limited in 2018 due to summer drought [34].…”
Section: Dry Matter Yieldsupporting
confidence: 87%
See 1 more Smart Citation
“…In the later years 2018 and 2019, however, there were no significant differences between REF and MUM [34]. This is in line with a finding from a recent study on intercropping miscanthus and legumes, in which similar effects were reported [47]. However, the potentially higher yielding variant REF was water limited in 2018 due to summer drought [34].…”
Section: Dry Matter Yieldsupporting
confidence: 87%
“…It is expected that there will be a trade-off between the achievement of high MYH of the intercropped plant stand (maize and miscanthus) in MUM in the first year and the achievement of high MYH of miscanthus from the second year onwards. This assumption is based on higher biotic (intercropping competition) and abiotic stress (e.g., drought) in the first year of establishment of miscanthus, which can significantly influence its morphological development and thus its suitability as a biogas substrate in the following years [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…(1) crop rotations [76,[125][126][127][128], (2) the intercropping of annual or perennial crops with legumes [86,[129][130][131][132], (3) the establishment of winter-annual species such as camelina (Camelina sativa L. Crantz) or perennial rye under annual crops [133][134][135], and (4) under maize-establishment of perennial energy crops such as miscanthus [115], the cup plant [136], and wild plant mixtures [122] among others [76,108,123].…”
Section: Spatial and Temporal Diversification Of Bcsmentioning
confidence: 99%
“…Moreover, methods of sowing cup plant under maize were developed . The intercropping of cup plant and maize during the first year of the cup plant establishment also promises to improve environmental performance of maize cultivation through decreased erosion and nutrient leaching …”
Section: Prospective Future Changes At Ephmentioning
confidence: 99%
“…68,131 The intercropping of cup plant and maize during the first year of the cup plant establishment also promises to improve environmental performance of maize cultivation through decreased erosion and nutrient leaching. 69,85,[135][136][137] Influence of the harvest time and ensilaging on properties of the cup plant At the end of the flowering period, which is September in Germany, the cup plant is chopped by a forage harvester with DIRECT DISC system© and transported to the storage location to be ensilaged. 126 Thus, it is harvested the same way and with the same equipment that is used for the maize harvest.…”
Section: Comparison Of Cup Plant and Maize Cultivation Practicesmentioning
confidence: 99%